The quality of life of men one year after radiotherapy for head and neck cancer: The fine details of experience matter. Issue 3 (August 2022) - Samsøe, G.; Bruvo, M.; Gerberg, L.
Abstract: Introduction: Radiographers and radiation therapists (RTT) meet cancer patients at the diagnosis, radiation treatment and late check-ups. This study aims to gain insight into men's experience concerning the quality of life one year after completing radiation therapy for head and neck cancer to contribute to radiographers' and RTT's understanding of patients' experiences during treatment. Methods: Six male head and neck cancer survivors were enrolled and interviewed one year after radiation therapy. Semi-structured interview transcriptions were coded to include statements about their experience of quality of life. Siri Næss' definition of quality of life is used as a theoretical framework. Results: This study generated four categories related to the personal experience concerned with the quality of life one year after radiotherapy treatment: Overwhelmed by information, Talking about mental well-being, Transitions - Cured but not healed, and The Fine Details to Quality of Life. There is a tendency that the patients do not express their emotions but express their assessments. Conclusion: This study contributes to a nuanced understanding concerning the possibility of high quality of life despite many late effects among men with head and neck cancer. The informants are overwhelmed by information before and after the course of treatment. The fine details in quality of life have a significant influence on the everyday life of head and neck cancer survivors. The findings have implications for radiographers' and RTT's communication, which requires knowledge of the patient's overall course of treatment. Implications for practice: The study indicates that it is vital for informants to be seen. Radiographers and RTT's must know of the patients' course of treatment and apply this in the dialogue with the patients.